2016
DOI: 10.1111/ijag.12244
|View full text |Cite
|
Sign up to set email alerts
|

Stress Relaxation and Refractive Index Change of As2S3 in Compression Molding

Abstract: As 2 S 3 is one of the chalcogenide glasses that have attracted increasing interests for compression molding applications. This paper is aimed to evaluate the stress relaxation behavior of As 2 S 3 above its glass transition temperature and calculate its refractive index change during cooling. First of all, creep tests were conducted with cylinder glass specimens at three different temperatures, in order to deduce the shear stress relaxation function by using the relationship with creep compliance function. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
37
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 44 publications
(59 reference statements)
1
37
0
Order By: Relevance
“…[20][21][22][23] Among them the most commonly used is CCT that can be handily implemented on hightemperature testing machines without complex specimen or fixture preparations. 9,16,24 These parameters were then fitted by phenomenological models and incorporated in finite element (FE) calculations to predict the molding force, 24 profile deviation, 11 and birefringence distribution 18 for industrial purposes. 9,16,24 These parameters were then fitted by phenomenological models and incorporated in finite element (FE) calculations to predict the molding force, 24 profile deviation, 11 and birefringence distribution 18 for industrial purposes.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…[20][21][22][23] Among them the most commonly used is CCT that can be handily implemented on hightemperature testing machines without complex specimen or fixture preparations. 9,16,24 These parameters were then fitted by phenomenological models and incorporated in finite element (FE) calculations to predict the molding force, 24 profile deviation, 11 and birefringence distribution 18 for industrial purposes. 9,16,24 These parameters were then fitted by phenomenological models and incorporated in finite element (FE) calculations to predict the molding force, 24 profile deviation, 11 and birefringence distribution 18 for industrial purposes.…”
mentioning
confidence: 99%
“…16,25 It was revealed by Avitzur that the interface friction during mental disc forging contributed considerably to the increase in the required forging force. 9 A practical method for merely achieving this displacement agreement is to adjust the interfacial friction coefficients in FE simulations (nearly zero, typically). For another, Joshi et al revealed that during constant-load compression the creep displacement of the glass specimen varied greatly with the interface friction.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…At such high temperature, in fact, the glass becomes liquid‐like where its relaxation time is extremely fast ( τ «seconds) so that the data obtained from the stress relaxation experiment is not sufficient and reliable for postprocessing. Based on the creep approach, the mold displacements are acquired and used to compute creep compliances . The drawback of this approach is that the temperature‐dependent viscoelasticity is not accomplished.…”
Section: Introductionmentioning
confidence: 99%